Pengaruh Financial Technology terhadap Akses Pembiayaan UMKM dengan Literasi Keuangan sebagai Variabel Moderasi di Kota Jambi - Haris Saputra, Muhammad; Permana, Kurnia (Program Studi Manajemen Keuangan Syariah, 2026)
The current study explores how fintech influences financing access for MSMEs and considers financial literacy as a moderating variable. The problem statement in the current research includes the limited financing access that represents a significant challenge for MSMEs and is especially common in regional settings. The methodology applied in this study is quantitative, with an explanatory research design adopted. The primary data collection technique used was the questionnaire distributed among 120 respondents who represented MSMEs located in Jambi City. To measure the constructs, a Likert scale was employed, while PLS-SEM analysis was conducted. The results showed that fintech significantly and positively impacts MSME financing access. In addition, financial literacy is proved to be significantly and positively associated with financing access. Additionally, financial literacy is established as a moderator that amplifies the effect of fintech on financing access. The coefficient of determination shows that the proposed model explains a considerable amount of the explained variance in financing access. Hence, it can be concluded that successful MSME financing access depends on both the use of fintech and the financial literacy of entrepreneurs. From the standpoint of policy implications, promoting financial literacy programs and developing a fintech ecosystem would contribute to the development of MSMEs.